5-HT2 and 5-HT3 receptors in the lateral parabrachial nucleus mediate opposite effects on sodium intake - De Gobbi, J. I. F.; Martinez, G.; Barbosa, S. P.; Beltz, T. G.; De Luca, L. A.; Thunhorst, R. L.; Johnson, A. K.; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2007)
The present study investigated the role of several 5-HT receptor subtypes in the lateral parabrachial nucleus (LPBN) in the control of sodium appetite (i.e. NaCl consumption). Male Holtzman rats had cannulas implanted bilaterally into the LPBN for the injection of 5-HT receptor agonists and antagonists in conjunction with either acute fluid depletion or 24-h sodium depletion. Following these treatments, access to 0.3 M NaCl was provided and the intakes of saline and water were measured for the next 2 h. Bilateral injections of the 5-HT2A receptor antagonist, ketanserin or the 5-HT2C receptor antagonist, mianserin into the LPBN increased 0.3 M NaCl intake without affecting water intake induced by acute fluid-depletion. Bilateral injections of the 5-HT2B receptor agonist, BW723C86 hydrochloride, had no effect on 0.3 M NaCl or water intake under these conditions. Treatment of the LPBN with the 5-HT2B/2C receptor agonist, 2-(2-methyl-4-clorophenoxy) propanoic acid (mCPP) caused dose-related reductions in 0.3 M NaCl intake after 24 h sodium depletion. The effects of mCPP were prevented by pretreating the LPBN with the 5-HT2B/2C receptor antagonist, SDZSER082. Activation of 5-HT3 receptors by the receptor agonist, 1-phenylbiguanicle (PBG) caused dose-related increases in 0.3 M NaCl intake. Pretreatment of the LPBN with the 5-HT3 receptor antagonist, 1-methyl-N-[8-methyl-8-azabicyclo (3.2.1)-oct-3-yl]-1H-indazole-3-carboxamide (LY-278,584) abolished the effects of PBG, but LY-278,584 had no effects on sodium or water intake when injected by itself. PBG injected into the LPBN did not alter intake of palatable 0.06 M sucrose in fluid replete rats. The results suggest that activation of the 5-HT2A and 5-HT2C receptor subtypes inhibits sodium ingestion. In contrast, activation of the 5-HT3 receptor subtype increases sodium ingestion. Therefore, multiple serotonergic receptor subtypes in the LPBN are implicated in the control of sodium intake, sometimes by mediating opposite effects of 5-HT. The results provide new information concerning the control of sodium intake by LPBN mechanisms. (C) 2007 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: 5-HT3; 5-HT2; angiotensin II; thirst; NaCl intake; LPBN